Novel MEF2C point mutations in Chinese patients with Rett (−like) syndrome or non-syndromic intellectual disability: insights into genotype-phenotype correlation - Wang, Jiaping (BMC Med Genet, 2018)
BACKGROUND: MEF2C (Myocyte-specific enhancer factor 2C) has been associated with neurodevelopmental disorders. This study aimed at delineating the clinical profiles of MEF2C gene mutations. METHODS: In total, 112 Chinese patients with intellectual disability (ID) were recruited, including 44 patients presented with Rett syndrome (RTT) or RTT-like syndrome, and 68 patients with non-syndromic ID. Targeted next-generation sequencing (NGS) was performed. Detailed clinical information was collected. RESULTS: Five heterozygous MEF2C gene mutations were identified, of which three were novel. The MEF2C mutant rate was 4.5% (5/112) in total, and 6.8% (3/44) in the RTT (−like) cohort. All patients with MEF2C gene mutation presented with cognitive impairment, gross motor delay, speech disorder and autistic features. Four patients had epilepsy, which responded well to antiepileptic drugs. One female was diagnosed with classical RTT, two females with RTT-like syndrome, and two males with non-syndromic ID. Generally, the phenotype of two males with relatively downstream mutations (c.565C > T, p.Arg 189*; c.766C > T, p.Arg 256*) was milder than that of three females with upstream mutations (c.48C > G, p.Asn16Lys; c.334G > T, p.Glu112* and c.403-1G > T). CONCLUSIONS: Our findings expanded the current understanding of the consequences of MEF2C dysfunctions, especially MEF2C point mutations. MEF2C mutations are associated with a broad clinical spectrum, ranged from classical RTT to non-syndromic ID. Through our study, it can be inferred that there is correlation between the phenotype and MEF2C-genotype, the mutation site. Overall, the MEF2C gene mutational analysis should be performed in ID cohort, especially in patients with features overlapped with RTT. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12881-018-0699-1) contains supplementary material, which is available to authorized users.